Steganography Using Quotient Value Differencing and LSB Substitution for AMBTC Compressed Images - Ji-Hwei Horng; Chin-Chen Chang; Guan-Long Li (IEEE Access, 2020)
In this paper, we apply quotient value differencing (QVD) and least significant bits (LSBs) substitution to hide secret data in an absolute moment block truncation coded (AMBTC) image. An AMBTC compressed image block consists of a high mean, low mean, and bitmap matrix. Based on the data structure of an AMBTC block, the proposed method includes three phases of embedding. In the first phase, QVD and LSB substitution are applied to embed secret digits into the low mean and high mean values. In the second phase, an additional bit is embedded by alternating the order of the low mean and high mean or not. Secret digits are embedded in the third phase by substituting the bitmap of smooth blocks. By leveraging the entire data structure of the AMBTC compressed code, the proposed method outperforms related works in embedding capacity.